For the Community, By the Community: Working with Youth to Develop a Physical Activity Environment Assessment Tool for First Nations Communities - Baillie, Colin (2014)
Thesis (Master, Kinesiology & Health Studies) -- Queen's University, 2014-10-15 23:50:13.325 Introduction: Several studies have demonstrated the benefits of physical activity (PA) for First Nations youth (Critchley et al., 2006; Tighe & McKay, 2012). It is also well-known that environmental factors like land-use mix and residential density play a critical role in the quality of PA opportunities available to youth (Ding, Sallis, Kerr, Lee, & Rosenberg, 2011). While the PA-environment link in urban centres is well understood, there has never been an exploration of the unique relationship First Nations youth have with their environment and how it might influence PA levels. Purpose: The purpose of this study was to explore the PA-environment relationship with First Nations youth to inform the development of a culturally relevant PA environment assessment tool for First Nations communities. Methods: Using the principles of community-based participatory research (CBPR) and Two-Eyed Seeing, First Nations youth (n=14) were trained in the art of Photovoice to take photos that illustrate ways in which the environment influences their PA. Youth also completed the Rural Active Living Assessment (RALA) tool. Next, the youth were asked to join a talking circle to share their experience of PA opportunities in their community as well as to discuss the RALA tool. Talking circles were analyzed for themes using NVivo software for Windows. Results: Youth co-researchers indicated that the First Nations community environment influences their PA through multiple ecological levels. The organization of themes using the socio-ecological model demonstrates that youth PA is influenced by the environment from the interpersonal to the policy level. This conceptual model will be used in addition to RALA tool commentary provided by youth co-researchers to develop a PA environment assessment tool. Discussion: This study was the first to explore the PA-environment link in First Nations communities from a First Nations youth ...